Pengaruh Website dan Branding Terhadap Peningkatan Kunjungan Wisatawan pada Destinasi Wisata Halal di Museum Keraton Sumenep Madura - Renanda Dian Nur Magfiroh; Muh Syarif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to analyze the influence of websites and branding on increasing tourist visits to halal tourist destinations at the Sumenep Palace Museum, Madura. The Sumenep Palace Museum holds substantial potential as a destination rich in local culture and history, with values capable of attracting both domestic and international tourists. However, despite its significant appeal, the number of tourist visits particularly from foreign tourists remains relatively low. In this rapidly developing digital era, optimizing the website as an information and promotional medium, along with a strong branding strategy, are essential aspects that must be developed to enhance the destination's appeal and encourage an increase in the number of visits. This study employs a quantitative approach with an explanatory method to elucidate the influence of two main variables: the website and branding. Primary data were collected through questionnaires distributed to respondents who had visited the Sumenep Palace Museum. This data collection aims to measure the impact of the website and branding on tourists' decisions to visit the Sumenep Palace Museum, as well as to identify opportunities for increasing visits through optimizing these two factors. It is expected that the results of this study will demonstrate that a well-designed, informative, and appealing website, along with consistent and strong branding, can increase tourists' interest in visiting. Furthermore, this research is intended to provide practical insights for destination managers in developing effective digital strategies, particularly those aligned with halal tourism principles, to increase visitor numbers and strengthen the Sumenep Palace Museum’s competitiveness as a leading tourist destination.